Evolution of resistive switching over bias duration of single Ag2S nanowires - ZHANG, HONGZHOU (My University, 2010)
We report experimental results of ultralow frequency photocurrent oscillation in individual ZnO nanowires. Consecutive photocurrent and photoluminescence measurements corroborate the process of capture and release of photogenerated holes by surface trap states. The dynamic process results in the oscillation of the thickness of surface depletion region, which is believed to be responsible for the observed photocurrent oscillation.
PUBLISHED
Keywords: AgS nanowires; Photocurrent